IKHTIBĀRU MAHĀRATI AL-QIRĀ'ATI FĪ TA‘LĪMI AL-LUGHATI AL-‘ARABIYYATI LIL-MUBTADI’ĪN: اختبار مهارة القراءة في تعليم اللغة العربية للمبتدئين - Ihwan Mahmudi; Mohamad Firman; Chevira Yasin Putri Indriyanti; Nurul Hidayah; Shohib Maulana; Maulidi Maulidi (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
Reading skills tests in Arabic language teaching constitute an essential component of language assessment, as they function not only to measure students’ comprehension of written texts but also to diagnose their reading abilities and guide instructional improvement. However, the forms of reading assessments specifically designed for beginner learners of Arabic as a foreign language remain insufficiently discussed in the literature. Therefore, this study aims to identify and analyze appropriate forms of reading skills tests for preparatory and beginner levels in Arabic language learning. This study employed a qualitative approach using library research methods. Data were collected from relevant journal articles, books, theses, dissertations, and other scholarly sources related to Arabic language assessment and reading instruction. The data were analyzed descriptively to classify the forms, objectives, and characteristics of reading tests suitable for novice learners. The findings reveal that reading assessments for beginner learners should be developed progressively, beginning with letter recognition, sound discrimination, vocabulary recognition, word-picture matching, sentence comprehension, simple text understanding, and basic reading analysis. Furthermore, effective reading tests should align with learners’ cognitive and linguistic development as well as with the basic competencies of Arabic reading instruction. The results of this study have significant implications for Arabic language education. They provide a conceptual framework and practical guidelines for teachers in designing valid and appropriate reading assessments for beginner learners. In addition, the findings contribute to curriculum development and facilitate more accurate diagnosis of students’ reading difficulties, thereby improving the effectiveness of Arabic language instruction for non-native speakers.